Perverses promiscuités ? Bains publics et cafés-concerts parisiens au second XIXe siècle - Lise Manin (Genre, Sexualité et Société)
In late 19th century Paris, bath houses and music-halls were reputed to be places where debauchery, prostitution, and offences against public decency were frequent. Even if these places effectively gave rise to homosexual encounters and soliciting, observers of the time represented them in many different ways. This is because these places not only promoted sexual encounters and sex trade, but also encouraged exhibitionism and voyeurism, due to the display of bodies more or less exposed, thus contributing in many ways to the construction of the erotic image attached to Paris. In this article, my aim is to understand the practices that these establishments hosted and to compare the different representations that they engendered, so that we may grasp the ‘eroticising’ dynamics of these spaces, the imagination of the erotic place, and the different motifs on which the discourse of Parisian Eros at the end of the 19th century are based.